Review article: Critical Care Airway Management eLearning modules. (16th November 2017) - Doshi, Deepak; McCarthy, Sally; Mowatt, Elizabeth; Cahill, Angela; Peirce, Bronwyn; Hawking, Geoff; Osborne, Ruth; Hibble, Belinda; Ebbs, Katharine
Abstract: The Australasian College for Emergency Medicine (ACEM) has recently launched the Critical Care Airway Management eLearning modules to support emergency medicine trainees in developing their airway management skills in the ED. A team of emergency physicians and trainees worked collaboratively to develop the eLearning resources ensuring extensive stakeholder consultation. A comprehensive resource manual was written to provide learners with knowledge that underpins the modules. ACEM provided project coordination as well as administrative and technical team support to the production. Although specifically developed with early ACEM trainees in mind, it is envisaged the resources will be useful for all emergency clinicians. The project was funded by the Australian Commonwealth Department of Health.